Influência das ferramentas de gestão comportamental na percepção de riscos de profissionais de diferentes setores industriais - Raddatz, Adriele Spacil (Universidade do Vale do Rio dos Sinos, 2016)
This article is a result of the need to understand if the worker perceives the risks of the environment in which he works. The main objective of this study is to analyze the challenges regarding the effectiveness of worker’s perception of risk in their activities, based on the perspective of professionals from different industry sectors, based on behavioral management tools. In addition, it also verify: the differences in the perception of risk and understanding about a behavioral approach and its tools among HSE professionals with the other sectors of the research respondents; and a relationship between behavioral management tools with a decrease in the number of occupational accidents and diseases. The methodology starts from a bibliographical research to base the study and verify a relation between what the theory proposes and what happens in practice. The research was done from a questionnaire, divided into five modules, to comprehend and evaluate the respondent’s perception of the topic. From the analysis of the results of the questionnaire and the theoretical basis of the research, it could be concluded that the objectives of the research were achieved. From the answers, it is estimated that the companies, in which the professionals of this research work, invest in safety and it is recognized by the workers, because only 12% of the statements diverged from the orientations found in the theoretical framework. It’s also concluded that the reduction in the number of work accidents is directly related to the use of behavioral safety tools.
Keywords: Segurança do trabalho; Erro humano; Percepção de riscos; Gestão comportamental; Safety; Human error; Perception of risks; Behavioral management